Analisis Komparasi Kinerja Keuangan Perusahaan Pertambangan Batubara Sebelum Dan Sesudah Akuisisi - Ardhyan Putra Christyanto; Sri Rakhmawati; Lisna Kustamtinah; Budiasih Budiasih; Heni Heryandini (Journal Of Business, Finance, and Economics (JBFE), 2023)
In 2016, Indonesia's economic growth increased from 4.88% to 5.02% due to an increase in exports which coal became one of the commodities that rose in price. This causes many coal mining companies are starting to expand their business. Many strategies are used to develop a business, one of them is acquisitions. This study aims to compare the company's financial performance before and after the acquisition in 2016 using the ratio of TATO, ROA, ROE, and NPM. This study used the Paired Sample T-Test. The samples in this study were PT Adaro Energy Tbk and PT Golden Energy Mines Tbk. This study compares the values of TATO, ROA, ROE, and NPM before and after the company makes an acquisition. Based on the Paired Sample T-Test, it was found that the TATO value before and after the acquisition did not have a significant difference, but the values of ROA, ROE, and NPM before and after the acquisition had significant differences. The comparison of the average value before and after the acquisition showed that there is an increase in the TATO, ROA, ROE, and NPM value of the companies.